Approaches to Sustainable Agriculture: A Retrospective Analysis for Soil Health Improvement: Sustainable Approaches for Soil Health - Katherasala, Srinivas (SAARC Journal of Agriculture, 2025)
Gaining insight into farmers' viewpoints is essential for attaining Sustainable Development Goals in agriculture. By actively involving farmers and integrating their perspectives, it is possible to foster novel strategies that enhance soil quality and bolster the agricultural ecosystem. It is possible to improve soil health and reduce reliance on outside inputs by using regenerative farming methods that are based on agroecological principles and precision farming technologies. Engaging in collaboration with researchers, policymakers, and agricultural communities is crucial to jointly developing creative artificial intelligence (AI), which has the potential to enhance economic expansion, reduce inefficiencies, and provide nutrients directly to plant roots. This transformation revolves around the recognition of solutions that effectively tackle the Sustainable Development Goals (SDGs) and advance the improvement of soil health. The study regenerated previous understanding and recommended that farmers investigate the intricate correlation between bacteria and nutrients to discover more effective approaches to soil management. Several natural alternatives include cyanobacteria, biofertilizers, plant growth-promoting rhizobacteria (PGPR), and livestock manure. Optimal soil health is crucial for the overall functioning and sustainability of entire ecosystems. The study emphasized the significance of prioritizing farmers' practices and adopting their perspectives to comprehend the real-time decision-making process. Furthermore, the study suggested some effective recommendations that farmers should receive to practice land tilling, smart farming adoption, residue management, and weed management. These potential strategies significantly enhance agricultural productivity.